Individual process management: a first step towards the conceptualisation of individual activities. (2016) - Leyer, Michael; Kronsbein, Daniel; Rosemann, Michael
Understanding activities of individuals is of major importance because their actions are the main foundation of economic activity. However, there is a lack of understanding with regard to how individual activities are characterised. Thus, we develop a first conceptual classification for individual activities extending the view on business processes. The classification scheme contains personal care, education, professional work, domestic work, leisure and travel as primary activities and individual organisation, procurement, information gathering and self-expression as secondary activities. We extend mainly prior literature on customer management by structuring processes of individuals independently from their status as customer. This enables new theoretical insights in the way companies can design their offers from a strategic point of view. Companies can use IPM to systematically analyse individual processes independent from specific products and services which is assumed to foster the development of innovative product and service offers.